Computer-aided construction at designing reinforced concrete columns as per EC - Zielińska, Monika; Grębowski, Karol (Zielona Góra: Uniwersytet Zielonogórski)
The article presents the authors` computer program for designing and dimensioning columns in reinforced concrete structures taking into account phenomena affecting their behaviour and information referring to design as per EC. The computer program was developed with the use of C++ programming language. The program guides the user through particular dimensioning stages: from introducing basic data such as dimensions, concrete class, reinforcing steel class and forces affecting the column, through calculating the creep coefficient taking into account the impact of imperfection depending on the support scheme and also the number of mating members at load shit, buckling length, to generating the interaction curve graph.
Keywords: computer program; structure designing; reinforced concrete columns; Eurocodes